Neurotrauma : Managing Patients with Head Injury. - Abelson-Mitchell, Nadine (Wiley, 2013)
Neurotrauma: Managing Patients with Head Injuries is a comprehensive, holistic, evidence-based approach to the primary, secondary and tertiary care of a person with neurotrauma. Using a patient-centred needs approach to enhance the quality of care of head injured patients, family and carers, this multidisciplinary book will enable the reader to apply the knowledge, skills and attitudes learned to the practice of neurotrauma in all settings. It explores: Anatomy and physiology of the brainPharmacology for neurotrauma patientsAssessment of the patien.